URGENSI PEMIDANAAN BAGI PELAKU PERDAGANGAN PENGARUH (TRADING IN INFLUENCE) DARI KALANGAN NON PEJABAT PUBLIK DALAM RANGKA PEMBERANTASAN TINDAK PIDANA KORUPSI - Joice Viladelfia; Rahel Octora (Dialogia Iuridica, 2021)
Cases of trading in influence in Indonesia have been rife with different modes, but there is no explicit regulation regarding the offense of influence trading so far. Trading in influence is mostly carried out by both state officials and non-public officials, who have access to public authorities. This paper discusses how the regulation of trading in influence by non-public officials is related to the enactment of the Corruption Act , as well as how the urgency of criminalizing the act of trading in influence (trading in influence) in order to optimize the eradication of Corruption. This research uses a juridical-normative method, with a statutory approach and a conceptual approach. Data collection is carried out by means of a literature study. This data processing is processed and analyzed qualitatively. The result of this research is that the legal system in Indonesia (in this case the Anti-Corruption Law) has not strictly regulated the actions of Trading Influence Influence, so it is necessary to revise the PTPK Law, to include the rules of Trading Influence. The formulation of the offense of trading in influence in Indonesia as part of a criminal act of corruption is considered very urgent in order to optimize the eradication of corruption.